2023
DOI: 10.1097/iae.0000000000003946
|View full text |Cite
|
Sign up to set email alerts
|

Imaging rhegmatogenous retinal lesions and peripheral vitreo-retinal interface with wide-field optical coherence tomography

Andrea Govetto,
J Sebag,
Sara Lucchini
et al.

Abstract: Purpose: Analyze the peripheral vitreo-retinal interface with widefield optical coherence tomography (WF-OCT). Methods: Retrospective chart analysis and WF-OCT in 120 consecutive cases of rhegmatogenous pathology. Results: There were 166 lesions in 120 eyes, including 106 horseshoe tears, 22 operculated (OH), 30 non-operculated (NOH) holes, 6 giant tears, and 2 peripheral lamellar defects followed for 6.1±1.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…Govetto et al retrospectively analyzed peripheral vitreoretinal interfaces with WF-OCT in cases with rhegmatogenous pathology [45]. The authors reported interesting findings concerning the relationship between the presence of specific types of peripheral retinal degeneration and the vitreoretinal interface status.…”
Section: Peripheral Retinal Degenerationmentioning
confidence: 99%
“…Govetto et al retrospectively analyzed peripheral vitreoretinal interfaces with WF-OCT in cases with rhegmatogenous pathology [45]. The authors reported interesting findings concerning the relationship between the presence of specific types of peripheral retinal degeneration and the vitreoretinal interface status.…”
Section: Peripheral Retinal Degenerationmentioning
confidence: 99%